A critical genre analysis of the user requirement specification report in the information technology industry / Shahizan Shaharuddin - Shahizan , Shaharuddin (2020)
While it has been established that discursive practices involving writing are highly situated and context-bound, few local studies have examined the processes involved in the construction of texts and the shaping of the intended text. Recent perspectives on writing as ways of working and acting, and texts as social action suggest that studying the processes behind the construction of a text could provide a clearer understanding of the discursive practices involved in the shaping of the text. This is seen as relevant to professional writing context in the present study as texts are often shaped to facilitate the social action of their users (Pare, 2015). Therefore, this study aims to investigate the processes involved in the construction of an information technology (IT) document called the User Requirement Specification (URS) report. This URS report is situated within the documentation practices of an IT development project involving the revamping of a client’s portal website. Using Rhetorical Genre Studies (Miller, 1984; Artemeva, 2009) as the main theoretical framework, the study employed interviews, document analysis and field notes to investigate the discursive practices involved in the shaping of this URS report. Thus, the study involved looking at the processes of text construction as well as into the text as an attempt at explaining the rhetorical and linguistics aspects of text construction. Based on the discourse analysis of interview transcripts report documents and the final URS report, findings revealed that the processes involved in the URS construction were based on three main concerns: the client’s needs and demands; the stipulated requirements and allowed format of the report (the template); and shared objectives of the project’s outcome. However, the writer and contributors to the text were able to exercise agency in recommending what could benefit the client and end-users of the portal in the long run. This is reflected in the discursive features of the final URS document. Examining the processes of the URS construction was useful to the study as it revealed the collective involvement of different teams and their communication that led to the production of URS report. It is hoped that the findings would be applicable in the context of technical report writing with helpful implications to professional context and the IT world.